2009
DOI: 10.1111/j.1540-8191.2008.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia in Cardiac Surgery-Patients with Symptomatic Factor V Leiden

Abstract: In 14 patients with symptomatic factor V Leiden who underwent cardiac surgery, we observed a considerable number of fatal and nonfatal thromboembolic events in the perioperative period and during a 32 months' follow-up. As conducted in three patients, continued anticoagulation with coumarin was safe and prevented perioperative thromboembolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…To assess the risk for poor surgical outcome associated with FVL, heterozygous carriers were compared with non-carriers. In contrast, the previous study, we did not observe a significant difference regarding fatal and nonfatal thromboembolic events in the postoperative period, which may be due to routine use of low molecular weight heparin postoperatively [15]. It should also be noted that one patient with FVL polymorphism from our study cohort developed fatal mesenteric ischemia postoperatively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To assess the risk for poor surgical outcome associated with FVL, heterozygous carriers were compared with non-carriers. In contrast, the previous study, we did not observe a significant difference regarding fatal and nonfatal thromboembolic events in the postoperative period, which may be due to routine use of low molecular weight heparin postoperatively [15]. It should also be noted that one patient with FVL polymorphism from our study cohort developed fatal mesenteric ischemia postoperatively.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, Massoudy et al . have reported that the incidence of perioperative and postoperative thromboembolic events was high in cardiac surgical patients with symptomatic heterozygous FVL disease and suggested preoperative screening [15]. To assess the risk for poor surgical outcome associated with FVL, heterozygous carriers were compared with non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that FVL polymorphism might be associated with an increased thrombotic risk and a decreased bleeding risk in patients that undergoing cardiac operations [15]. The incidence of thromboembolic complications during perioperative and postoperative period in cardiac surgical patients was related with heterozygous FVL mutation [16]. In # # [13] did not find a statistically significant difference with postoperative thromboembolic complications, which may be due to routine heparin administration postoperatively.…”
Section: Discussionmentioning
confidence: 89%
“…It has been speculated that FVL polymorphism might be associated with an increased thrombotic risk and a decreased bleeding risk in patients that undergoing cardiac operations [15]. The incidence of thromboembolic complications during perioperative and postoperative period in cardiac surgical patients was related with heterozygous FVL mutation [16]. In MTHFR C677T MTHFR A1298C PT G20210A FVL HET HET WT WT HET HET WT HET HET HET WT HET HET HET WT HET HET HET WT WT HET HET HET WT HET HET WT WT HET HET WT WT HET HET WT WT HET HET WT HET HET HET WT WT HET HET WT WT HET HET WT WT HET HET HET WT FVL=Factor V Leiden, PT 20210A=Prothrombin gene mutation, MTHFR=Methylenetetrahydrofolate reductase, HET=heterozygous, WT=wild type # contrast, Emiroglu et al [13] did not find a statistically significant difference with postoperative thromboembolic complications, which may be due to routine heparin administration postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…1,11–14 Thus although factor V Leiden may contribute to venous thrombosis, most current literature indicates that the increased risk of hypercoagulability conferred by factor V Leiden is outweighed by current surgical management, including the use of chemo- and mechanoprophylaxis of venous thrombosis in the postoperative period. 15 However, most agree that patients who experience multiple thrombotic events must be placed on a long-term anticoagulation regimen after the perioperative period, as was done with this patient. 16,17 Hereditary thrombophilia was not considered to be significant enough to alter the time course of antithrombotic therapy, and heterozygosity of factor V Leiden by itself is not an indication for long-term anticoagulation without associated indications.…”
Section: Discussionmentioning
confidence: 97%